2010
DOI: 10.1038/sj.bjc.6605500
|View full text |Cite
|
Sign up to set email alerts
|

C20orf20 (MRG-binding protein) as a potential therapeutic target for colorectal cancer

Abstract: BACKGROUND: Colorectal cancer is one of the most common causes of cancer death worldwide. Using cDNA microarray containing 23 040 genes, we earlier investigated gene-expression profiles in 11 colorectal cancers for the purpose of better understanding of colorectal carcinogenesis as well as development of novel diagnostic and therapeutic strategies. MRG-binding protein (MRGBP) or C20orf20, encoding a subunit of TRRAP/TIP60-containing histone acetyltransferase complex, was up-regulated in the majority of colorec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
43
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 14 publications
7
43
1
Order By: Relevance
“…Previous studies suggested that upregulated MRGBP might promote proliferation of colorectal cancer cells through the regulation of BRD8. 7 Furthermore, MRGBP could regulate stability and/or synthesis of both TIP60/HAT complex and HDACs complexes, which are associated with tumor occurrence and advance, as well as aggressive biological behaviors. [24][25][26][27] We previously revealed that MRGBP expression was significantly upregulated in PanCa samples and cell lines.…”
Section: Mrgbp Plays Positive Roles In Pancreatic Cancermentioning
confidence: 99%
“…Previous studies suggested that upregulated MRGBP might promote proliferation of colorectal cancer cells through the regulation of BRD8. 7 Furthermore, MRGBP could regulate stability and/or synthesis of both TIP60/HAT complex and HDACs complexes, which are associated with tumor occurrence and advance, as well as aggressive biological behaviors. [24][25][26][27] We previously revealed that MRGBP expression was significantly upregulated in PanCa samples and cell lines.…”
Section: Mrgbp Plays Positive Roles In Pancreatic Cancermentioning
confidence: 99%
“…This colorectal cancer study showed that a reduction of C20orf20 expression through stable short-hairpin RNA inhibited proliferation in the colon carcinoma lines HCT116 and SW480 (shown by a 10% decrease in S-phase replicating cells), without evidence of apoptosis (Yamaguchi et al , 2010). We investigated whether C20orf20 knockdown yielded similar results in cSCC and whether any effect on normal keratinocytes was observed.…”
Section: Resultsmentioning
confidence: 99%
“…In human colon cancer, MRGBP was upregulated in the majority of the cancers. Inhibition of MRGBP with shRNA in vitro resulted in an inhibition of cell growth (Yamaguchi et al, 2010). High levels of MRGBP expression were observed more frequently in human colonic carcinomas (45%) than adenomas (5%), linking its role to malignant properties of colorectal tumors (Yamaguchi et al, 2011).…”
Section: Actin/act1/act1mentioning
confidence: 99%
“…These subunits are overexpressed in colon cancer (Yamada and Rao, 2009;Yamaguchi et al,2010Yamaguchi et al, , 2011Carlson et al, 2003;Lauscher et al, 2007;Graudens et al, 2006;Ki et al, 2007). Brd8 plays a role in survival and/or drug resistance of cultured colon cancer cells.…”
Section: Relevance To Colon Cancermentioning
confidence: 99%
See 1 more Smart Citation